Synthesis, characterization and development of reduced graphene oxide incorporated zinc oxide nanocomposite for cellulose-based humidity sensing application / A. Shamsul Rahimi A. Subki - A. Subki, A. Shamsul Rahimi (2024)
In this study, the practicality of utilizing zinc oxide (ZnO) nanostructured powder as a humidity-sensitive sensing material for resistive humidity sensors was investigated. The impurity amalgamation and construction of nanocomposite with the introduction of reduced graphene oxide (rGO) have been explored to enhance the pristine ZnO nanostructured powder-based humidity sensor performance. Pristine and impuritiesinduced nanostructured powder have been successfully synthesized through a benign and facile low-temperature ultrasonicated solution immersion method. The humidity sensor was constructed by a simple and inexpensive brush printing technique which employed cellulose filter paper as a substrate, synthesized nanostructured powders or nanocomposite as sensing material, and transparent paper glue as a binding agent. The structural, morphological, and chemical changes of the synthesized nanostructured powder were characterized through X-ray diffraction, field emission scanning electron microscopy, high-resolution transmission electron microscopy, energy dispersive X-ray spectroscopy,